Bad habits in the light of comrades' groups (International Journal of Psychosocial Rehabilitation, 2020)
One of the issues rooted in the depths of a person is his social nature. Cases of collective belonging and agglomeration within the framework of a specific grouping all stem from the instinct of the necessity of belonging. The need for belonging and a sense of security is a human obsession, man’s work throughout the ages. He is always searching for communication with others to satisfy this need. Since the childhood of an individual, he has gradually developed the ability to establish social relationships with others. It can be said, and until recently, that the process of socialization in societies, with its formal and informal institutions, such as the family, the school, the religious institution, the media, and the group of comrades, was an affordable and specific process, and the features and procedures undertaken by these institutions are considered the womb in which the features of human identity and values are formed and its trends. As the individual is born in a group, and the group assists the human being in forming his behavior, and the group is affected by it in a negative or positive way, as the family and the school play a positive role in directing the cohort community towards the best, and the relationships between the peers contribute to the cognitive, social, and emotional maturity if it is better directed. A person cannot be proud of the bad habits he practices, just as he is always in conflict with himself in order to try to change it and get rid of it, even if he does not express this matter in front of others, and no person can be free from bad habits, regardless of his position and status. And society is alienated from such bad habits and alienated from its owner. Humans are innately willing to be guided by the behavior of those close to them and the friends they eat with, as many studies have found that some may eat more food when they are accompanied by binge friends. People may attribute their appetite for food to taste, price, or hunger and do not realize that the real cause is friendship. The current research aimed at identifying the level of social problems, shedding more light on the group of comrades in random neighborhoods, and identifying the role that parents play in limiting the incidence of the individual in some wrong groups.